The Boma: Covid-19: Finding the origins of a pandemic - International Livestock Research Institute (International Livestock Research Institute, 2021)
Covid-19 has had the world at a stand-still since early last year and yet we are still trying to find out how the pandemic started. Did the virus come directly from a bat, a different wild animal, was it spread by frozen food, or was it even leaked from a lab? A report published at the end of March by the World Health Organization and a joint team of scientists begins to unravel the mystery of the origins of the coronavirus, SARS-CoV-2. Tim Offei-Addo sat down with Hung Nguyen-Viet, co-leader of the Animal and Human Health Program at ILRI, to discuss his experience traveling to Wuhan as part of the team trying to find the origins of the pandemic.